Organic fertilizer substitution altered the waxy maize grain quality and aroma volatiles formation by the integrated transcriptomic and metabolomic analyses - Xiaoqiang Zhao; Qiang Chai; Wen Yin; Hong Fan; Wei He; Cai Zhao (Frontiers in Plant Science)
Organic fertilizer substitution is an important agronomic strategy to improve waxy maize quality and aroma, while their regulatory mechanisms remain unclear. Herein, volatiles identification combined with transcriptomics to investigate grain quality and aroma formation mechanism across waxy maize “Jingkenuo 2000” at 20 days after pollination under 100% inorganic N fertilizer (IF), 100% organic N fertilizer (OF), organic fertilizer substituting 50% inorganic N fertilizer (OF_IF). Using HS-SPME-GC/MS, 20 differentially accumulated volatiles were identified, among them, volatile alkanes and esters compounds were the main volatile metabolites, accounting for 30% each, IF decreased esters metabolites (61.0%), OF increased alkanes compounds (6.5%), OF_IF had the highest esters abundance (i.e., E-2-hexenyl benzoate, hexadecanoic acid, methyl ester, octadecanoic acid, ethyl ester, octadecanoic acid, thyl ester, tetradecanoic acid, ethyl ester, and hexadecanoic acid, ethyl ester). RNA-sequencing analysis identified 1,923 unique differentially expressed genes (DEGs), and 18 core conserved DEGs among all comparison groups, which were potential candidate genes for breeding. 43 DEGs controlling sugar, amino acids, N-glycan, carotenoid, vitamin B6, and folate biosynthesis and metabolism. The interaction network analysis further revealed the complexity of quality and aroma formation. The findings provide valuable insights into grain quality and volatiles formation during waxy maize grain development under organic fertilizer substitution.